Effect Of Heel Effect Anode On Image Homogeneity Based On X-Ray Collimation Light Beam Area - Rosidah, Siti; Felayani, Fadli (Sean Institute, 2022)
The Anode Heel effect is the difference in X-ray intensity due to the slope of the anode target plane. The X-ray intensity at the cathode is more significant than on the anode side. Differences in X-ray intensity affect the radiographic image, especially the density value. Heel Effect Anodes in radiological examinations are used on objects with different thicknesses. This study aimed to determine the Effect of Heel Effect Anodes on Image Homogeneity Based on X-Ray Collimated Light Beam Areas. The samples used three collimation area sizes (18x24 cm, 24x30 cm, 35x43cm). Each collimation area is carried out three times exposure. The resulting radiograph is divided into several quadrants, and density measurements are taken. Then the analysis was carried out by finding the difference in the density of each quadrant on each radiograph by performing univariate analysis, and then bivariate analysis was carried out. Homogeneous images can be seen from the density difference value on one radiograph that cannot be more than 0.1. The results showed a significant effect from the anode to the cathode on the collimation area of ​​18x24 cm, 24x30 cm, and 35x43cm on the density value with p = 0.000. There is a difference in the anode to cathode relationship category concerning density; the collimation area of ​​18x24 cm has a reasonably strong relationship.In contrast, the relationship is strong in the collimation area of ​​24x30 cm and 35 x 43 cm. The relationship is positive. The closer to the cathode, the greater the density. The greater the collimation area, the stronger the difference in density homogeneity on the radiograph. The closer to the cathode, the greater the density produced. There is a significant difference between the area of ​​the irradiation field and the density, and it is recommended that during an inspection, the thick object is placed on the cathode side, and the thin object is placed on the anode side to produce optimal image quality.